2018
DOI: 10.1287/trsc.2017.0804
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Traffic-Theoretic Network Loading Model Suitable for Large-Scale Network Analysis

Abstract: This paper formulates an analytical stochastic network loading model. It is a stochastic formulation of the link transmission model (LTM), which itself is an operational formulation of Newell's simplified theory of kinematic waves. The proposed model builds on an existing initial model. It proposes a formulation with enhanced scalability. In particular, compared with the initial model, it has a complexity that is linear rather than cubic in the link's space capacity. This makes it suitable for large-scale netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…Last but not least, the financial equivalent for the replacement of the upper roadway layer or the whole roadway construction is based on approved cost databases, but it can´t be generalized to all roads of the same class (each road administrator of the given road uses apart from these cost databases its own pricelists). In spite of all these deficiencies, the analytical model also brings into the calculation of total costs I 2 other factors in accordance with [5,[18][19][20][21], which have a major effect on the negative impacts of the diverted traffic flow. These externalities are subsequently expressed by the financial equivalent, of which is the road administrator in case of higher intensities (proportion) of heavy freight vehicles more loaded compared to the road management in normal operation.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, the financial equivalent for the replacement of the upper roadway layer or the whole roadway construction is based on approved cost databases, but it can´t be generalized to all roads of the same class (each road administrator of the given road uses apart from these cost databases its own pricelists). In spite of all these deficiencies, the analytical model also brings into the calculation of total costs I 2 other factors in accordance with [5,[18][19][20][21], which have a major effect on the negative impacts of the diverted traffic flow. These externalities are subsequently expressed by the financial equivalent, of which is the road administrator in case of higher intensities (proportion) of heavy freight vehicles more loaded compared to the road management in normal operation.…”
Section: Discussionmentioning
confidence: 99%
“…Probabilistic link model formulations with traffic-theoretic foundations include Boel and Mihaylova (2006); Sumalee et al (2011); Liu (2012, 2013); Osorio et al (2011); Deng et al (2013); Laval and Chilukuri (2014); Laval and Castrillón (2015); Osorio and Flötteröd (2015); Lu and Osorio (2018); Lu (2020). The main approaches have been the introduction of randomness in the cell transmission model, extensions of the variational theory of Daganzo (2005) and the use of probabilistic queueing theory (Olszewski, 1994;Heidemann, 2001;Viti and Van Zuylen, 2010;Osorio et al, 2011;Osorio and Flötteröd, 2015;Lu and Osorio, 2018). Another stream of research in the estimation of queue length distribution is based on observed data collected from probe vehicles Cetin, 2009, 2011;Comert, 2013Comert, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…For a link with space capacity , the model complexity is in the order of O( 3 ). Lu and Osorio (2018) have extended the formulation of Osorio and Flötteröd (2015), leading to a model with complexity in the order of O( ). This is a formulation that scales linearly with the link's space capacity, making it efficient and appropriate for large-scale network analysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations